(untitled) (Journal of the College of Basic Education, 2022)
There is no doubt that oil, since its discovery, has been at the top of the priorities of countries in their political movement and struggles in order to extend influence and hegemony. Rather, the relationship of oil with force has turned into a dialectical relationship of a reflexive nature. In order to have power, you have to control the oil sources, and in order to control the oil sources, you need more oil. Power. Oil colonialism in Iraq is the main characteristic of the form of colonial control, because Iraq formed a center of gravity for global colonial oil interests and was one of the causes of the First World War and the axis of the international conflict after its end as one of the main spoils. The victors in World War I shared the spoils of war, and Iraq fell into Britain’s share.